2022
DOI: 10.1037/per0000584
|View full text |Cite
|
Sign up to set email alerts
|

Should the demonstration of improved patient outcome be necessary to overhaul diagnostic approaches?: Comment on Bach and Tracy (2022).

Abstract: I will argue in this commentary that it is premature to change the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition approach toward diagnosing personality disorders to the alternative model for personality disorders (AMPD) because such a change in determining personality pathology will be disruptive, and such a disruption is warranted only when it can be demonstrated that patient outcomes are better. I briefly review studies comparing unstructured clinical evaluations with semistructured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…We agree that these are all vital steps for improvement and refinement, and no doubt should be part of the research agenda going forward. In addition, as rightly pointed out by Zimmerman (2022b) and Vanwoerden and Stepp (2022), the AMPD must demonstrate at least similar, if not superior, patient outcomes as the categories. Although convergence studies have been conducted, superiority studies have not.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We agree that these are all vital steps for improvement and refinement, and no doubt should be part of the research agenda going forward. In addition, as rightly pointed out by Zimmerman (2022b) and Vanwoerden and Stepp (2022), the AMPD must demonstrate at least similar, if not superior, patient outcomes as the categories. Although convergence studies have been conducted, superiority studies have not.…”
Section: Discussionmentioning
confidence: 93%
“…More specifically, they call for additional AMPD assessment tools (beyond self-report) and their dissemination among clinicians, adaptation of treatment manuals to the AMPD, education in the AMPD, as well as research that maps neurobiology onto the AMPD. Zimmerman (2022b) is less enthusiastic about the promise of the AMPD and suggests a single criterion to evaluate clinical utility, namely, improvement in patient outcome. He argues that such a dramatic, substantial change to the nosology cannot be justified, even if more valid, without demonstration in this one domain.…”
Section: Special Section Findings and Recommendationsmentioning
confidence: 99%
“…Despite studies into the perceived usefulness of these approaches, almost no work has actually demonstrated increased treatment efficacy. This undertaking would require randomized controlled trials across multiple sites ( 162 ), which would investigate changes in personality functioning and impairment through trait and distress informed treatments ( 161 ).…”
Section: Clinical Utility Of Dimensional Models: Challenges and Oppor...mentioning
confidence: 99%
“…Even within research settings where reliable clinical measures have been developed and are used, the clinical utility and implications of differences in severity remain largely untested [12]. To the best of our knowledge, no randomized controlled trial has randomized patients with personality disorders of the same severity level into two distinctly different experimental and control groups, and based on the evidence of a strong common factor across bona fide treatments, it is not obvious that we should expect to find large effect differences across different levels of severity [13]. This knowledge gap in the implications of the ICD-11 for treatment may be even wider when it comes to children and adolescents.…”
Section: Mentalization and Personality Functioningmentioning
confidence: 99%